Service Quality in Electricity Distribution in Brazil: A Malmquist Approach - Alexandre Marinho; Marcelo Resende (Center for Economic Studies and ifo Institute (CESifo), 2016)
The paper undertakes a dynamic analysis for service quality in the electricity distribution in Brazil between 2010 and 2014 based on Malmquist indexes constructed upon Data Envelopment Analysis (DEA) distance functions. The motivation for the less usual consideration of efficiency frontiers for service-quality builds on previous static applications in the context of telecommunications as given by Façanha and Resende (2004), Resende and Façanha (2005) and Resende and Tupper (2009). The analysis treats undesirable technical indicators as inputs and desirable consumer satisfaction indicators as outputs. The bootstrap- corrected Malmquist indexes indicated that service quality is an important concern as the evidence respectively indicates quality deterioration in 38.1 %, quality stagnation in 40.5 % and quality improvement only in 21.4 % of the cases. When one decomposes the Malmquist index, the evidence does not suggest relevant frontier shifts and indicates a dominant role for the catch-up effect.
Keywords: 330; service quality; consumer satisfaction; electricity distribution; Brazil